2016
DOI: 10.1097/j.pain.0000000000000220
|View full text |Cite
|
Sign up to set email alerts
|

Ultramicronized palmitoylethanolamide reduces viscerovisceral hyperalgesia in a rat model of endometriosis plus ureteral calculosis

Abstract: The effects of ultramicronized palmitoylethanolamide were evaluated on pain behaviours and markers of mast cell (MC) activity in a rat model of endometriosis plus ureteral calculosis (ENDO+STONE)-induced viscerovisceral hyperalgesia (VVH). Female Sprague-Dawley rats that underwent surgical induction of endometriosis were randomly assigned to receive active (ultramicronized palmitoylethanolamide 10 mg·kg(-1)·d(-1), orally) or placebo treatment for 25 days. At day 21, they underwent ureteral stone formation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 63 publications
(48 reference statements)
3
21
0
Order By: Relevance
“…This observation may depend on the time of sampling or the small number of samples used. Although further studies on the present ex vivo model are merited, one should keep in mind that PEA‐um has been reported to decrease MC‐derived vasoactive mediators, both in vitro and in vivo . Moreover, the effect of systemic administration of PEA‐um on clinical signs sustained by dilation of cutaneous capillary vessels, including erythema, and the wheal and flare reaction, has been demonstrated in dogs …”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This observation may depend on the time of sampling or the small number of samples used. Although further studies on the present ex vivo model are merited, one should keep in mind that PEA‐um has been reported to decrease MC‐derived vasoactive mediators, both in vitro and in vivo . Moreover, the effect of systemic administration of PEA‐um on clinical signs sustained by dilation of cutaneous capillary vessels, including erythema, and the wheal and flare reaction, has been demonstrated in dogs …”
Section: Discussionsupporting
confidence: 92%
“…Although further studies on the present ex vivo model are merited, one should keep in mind that PEA-um has been reported to decrease MC-derived vasoactive mediators, both in vitro and in vivo. 23,28,40,43,51 Moreover, the effect of systemic administration of PEA-um on clinical signs sustained by dilation of cutaneous capillary vessels, including erythema, and the wheal and flare reaction, has been demonstrated in dogs. 7,9 In the present ex vivo model, exposing skin organ cultures to PEA-um for 96 h did not elicit any change in either the epidermal or dermal skin compartments, in terms of epidermal thickness or keratinocyte proliferation, the same pattern of keratinocyte differentiation markers, unchanged MC density and degranulation state, compared to vehicle-treated samples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study found that the group's treatment led to decreased pain behaviors and decreased NGF in the mice [128]. Luvone et al [129] found NGF to play a role in both endometriosis- and ureteral calculosis-related pain. Specifically, ultramicronized palmitoylethanolamide (PEA-um) was noted to decrease pain-related behaviors in rat models of endometriosis and ureteral calculosis [129].…”
Section: How Do Pharmacological Interventions Take Advantage Of Pamentioning
confidence: 99%
“…Luvone et al [129] found NGF to play a role in both endometriosis- and ureteral calculosis-related pain. Specifically, ultramicronized palmitoylethanolamide (PEA-um) was noted to decrease pain-related behaviors in rat models of endometriosis and ureteral calculosis [129]. The effect of PEA-um was linked to decreases in NGF (as well as other factors) [129].…”
Section: How Do Pharmacological Interventions Take Advantage Of Pamentioning
confidence: 99%